Mertensinema iberica gen. n., sp. n. (Nematode, Trichostrongylidae, Mertensinematinae subfam. n.) — паразит кавказской саламандры - Шарпило, В.П. (Вестник зоологии, 1976)
A description and drawing of Mertensinema iberica gen. n., sp. n., a parasite of Mertensiclla caucasica, are given in the article. Diagnoses of the new genus and subfamily are presented. Characteristic features of the described Nematode are as follows: the bursa is whole, without lobes, long spicules splitted along the greater part of its length into three acinaciform processes, presence of gubernaculum, etc.